Clinico-angiographic profiles and in-hospital outcomes of non-ST segment elevation myocardial infarction in Kurdistan Region of Iraq - Mohammad, Ameen M; Issa, Haval A; Saeed, Saad Y (Journal of Contemporary Medical Sciences, 2022)
Objectives: This work aimed to study the clinical, angiographic profiles and in-hospital outcomes of NSTEMI cases in Duhok, Iraq. Methods: This prospective study involved 283 patients with NSTEMI who were admitted to Azadi teaching hospital/Azadi heart center in Duhok, Kurdistan region of Iraq, between 2021 and 2022. The patient's demographic variables, major cardiovascular risk factors (smoking, hypertension, diabetes mellitus, hyperlipidemia and family history of coronary artery disease), clinical presentation, past history of myocardial infarction/ previous percutaneous coronary intervention (PCI) and drug history were collected. The GRACE risk score was calculated for each patient. Patients were followed up regarding the management strategies (whether conservative or invasive approach), and in-hospital complications and outcomes. Results: The mean GRACE score was 142±26. 70% of cases underwent coronary angiography/ angioplasty, with a mean time to the coronary intervention of 8 days. 17% of the sample had developed different cardiovascular complications, with heart failure being the most common. The mortality rate was 7.4%. Conclusion: The study demonstrated higher complications and mortality rates, especially among patients with higher GRACE scores, compared to rates found in most available studies, particularly in western countries. This finding could be secondary to a suboptimal coronary intervention for NSTEMI in terms of time to intervention and the proportion of patients who underwent it.